A mortality risk score for septuagenarians undergoing orthotopic heart transplantation. Issue 3 (4th January 2021) - Diaz‐Castrillon, Carlos E.; Seese, Laura; Hong, Yeahwa; Dufendach, Keith; Hickey, Gavin; Sultan, Ibrahim; Kilic, Arman
Abstract: Background: With septuagenarians undergoing orthotopic heart transplantation (OHT) more frequently, we aimed to develop a risk score for 1‐year mortality in this population. Methods: Septuagenarian OHT recipients were identified from the UNOS registry between 1987 and 2018. The primary outcome was 1‐year post‐OHT mortality. Patients were randomly divided into derivation and validation cohorts. Associated covariates were entered into a multivariable logistic regression model. A risk score was created using the magnitudes of the odds ratios from the derivation cohort, and its 1‐year post‐OHT mortality prediction capacity was tested in the validation cohort. Results: A total of 1156 septuagenarians were included, and they were randomly divided into derivation (66.7%, n = 771) and validation (33.3%, n = 385) cohorts. An 11‐point risk score incorporating 4 variables was created, which included mechanical ventilation, serum bilirubin, serum creatinine, and donor age. The predicted 1‐year mortality ranged from 4.2% (0 points) to 48.1% (11‐points) ( p < .001). After cross‐validation, the c‐index was 0.67 with a Brier score of 0.10. Risk scores above 3 points portended a survival disadvantage at 1‐year follow‐up ( p < .001). Conclusions: This 11‐point risk score for septuagenarians is predictive of mortality within 1‐year of OHT and has potential utilization in improving recipient evaluation and selection of elderly patients.